Systemic Risks of Management in the Implementation of State Policy on Education and Science: Analysis of Problem Situation, Risks and their Identification - Elena Mikhailovna Anokhina; Yury Vasilyevich Kosov; Vladimir Georgievich Halin; Galina Vasilyevna Chernova (Управленческое консультирование, 2018)
Significant changes occurring in the management by Russian education and science, accompanied by the appearance and the possibility of various risks. Since education and science can be regarded as an integral single system of interrelated elements forming it, object of consideration is the systemic risks. They are caused by the education and science management as a single system and their implementation may lead to the destruction and even death of system of the Russian education and science. The article analyzes the problem situation related to the status and development of Russian science and higher education in the conditions of their reforming, of the state policy in the field of science and training. Analysis of the values and the dynamics of the main indicators of the status and development of the Russian science and higher education are given also. The results showed the following. Management decisions for the implementation of the measures of state policy on education and science are accompanied really by various risks, including system risks. The article presents the author’s approach to the definition of systemic risk, described by certain parameters. Based on the analysis significant system management risks associated with the conduct of Russian state policy in the sphere of education and science are highlighted. Identification of the relevant systemic risks is given in the context of concrete management decisions. The possibility of realization of systemic risk is confirmed by real examples.